2018
DOI: 10.1007/s12035-018-1445-6
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated CRMP2 Regulates Spinal Nociceptive Neurotransmission

Abstract: The collapsin response mediator protein 2 (CRMP2) has emerged as a central node in assembling nociceptive signaling complexes involving voltage-gated ion channels. Concerted actions of posttranslational modifications, phosphorylation and SUMOylation, of CRMP2 contribute to regulation of pathological pain states. In the present study, we demonstrate a novel role for CRMP2 in spinal nociceptive transmission. We found that, of six possible post-translational modifications, three phosphorylation sites on CRMP2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 73 publications
2
63
0
Order By: Relevance
“…We tested three different ratios of CRMP2/edonerpic maleate: no binding was detected between CRMP2 and edonerpic maleate (Figure 1(a)). (S)-lacosamide, an inhibitor of CRMP2 phosphorylation [3,5,7], was used as a positive control at the same concentrations and showed binding to CRMP2 (not shown), consistent with our previously published finding [7]. Next, we used microscale thermophoresis (MST), a method for the biophysical analysis of biomolecular interactions, but were unable to detect any interaction between edonerpic maleate and CRMP2 with this method either (not shown).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…We tested three different ratios of CRMP2/edonerpic maleate: no binding was detected between CRMP2 and edonerpic maleate (Figure 1(a)). (S)-lacosamide, an inhibitor of CRMP2 phosphorylation [3,5,7], was used as a positive control at the same concentrations and showed binding to CRMP2 (not shown), consistent with our previously published finding [7]. Next, we used microscale thermophoresis (MST), a method for the biophysical analysis of biomolecular interactions, but were unable to detect any interaction between edonerpic maleate and CRMP2 with this method either (not shown).…”
supporting
confidence: 82%
“…Edonerpic maleate was found to disrupt CRMP2 tetramers [10]. Our previous body of work has established a role for phosphorylated and non-phosphorylated CRMP2 in control of voltage-gated calcium and sodium channels [1,[3][4][5][6][7][8][13][14][15][16][17][18][19][20][21][22]. Therefore, we tested the effect of edonerpic maleate on these channels.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that CRMP2 phosphorylation by cyclin dependent kinase 5 (Cdk5) affected the frequency of sEPSCs in the spinal dorsal horn [73]. This function was hypothesized to be linked to CRMP2's regulation of both the N-type voltage-gated calcium channel (CaV2.2) as well as NaV1.7.…”
Section: Crmp2 K374a/k374a Has No Impact On Basal Spinal Spontaneous mentioning
confidence: 99%